Applied research on enhancing respiratory muscle strength of synchronized swimmers by using respiratory muscle trainer - An, J.; Fan, Y. (Exercise Biochemistry Review, 2018)
Objective In research to date , powerbreath training to be tested were useful to improve the athletics` ability for training the breathe muscles, by the way to optmizing the Breathing technique.To further improve the synchronize swimming athletes` powerbreath of BeiJing,tenhancing the athletics level and express ability of whole team, to succeed in the finals.